DEFINITION OF NEW ASPECTS OF CHANGING THE ECOLOGICAL STATE OF A SURFACE WATER OBJECT - Kovalenko, S.; Ponomarenko, R.; Tretyakov, O.; Tytarenko, A.; Ivanov, Y. (Municipal economy of cities. Series: «Economy science», 2022)
The article analyzes the qualitative composition of the surface water body, namely the Seym River in Chernihiv and Sumy regions, to determine changes in its ecological status. Possible causes of its pollution have been identified. Statistical and systematic analysis of environmental change was conducted on the basis of the interactive map «Monitoring and Environmental Assessment of Water Resources of Ukraine» of the State Agency of Water Resources of Ukraine in the period from January 2012 to December 2020 based on data from four observation posts of the Seym. The purpose of the study is to identify new temporal and spatial trends in the concentration of major pollutants along the Seym River within Sumy and Chernihiv regions to ensure the possibility of using the results as baseline data in subsequent stages of the study to apply the basin principle of water management. The content of the main indicators was analyzed: polyphosphates, ammonium, nitrates and nitrites, phosphates and sulfates. Data on water intake control from four posts within the Seym River were studied. The increase in the content of ammonium ions every year indicates a deterioration in the sanitary condition of the water in the Seym River. According to the data on biological oxygen consumption in the Seym River, there is a constant deterioration of the oxygen regime at four posts. The increase in nitrate content is associated with an increase in the area of nitrate washout. The decrease in the content of phosphates and sulphates in the Seym River at the observation posts may be due to the fact that the population in the settlements is decreasing every year. From the point of view of basin management, it is expedient to establish an additional point of quality control of water discharges. In the future, the results of the study can be used in the development and implementation of a reliable and effective model for forecasting the ecological status of the Seym River. The results obtained during the study make it possible to state that the ecological condition of the Seyjm River, one of the important tributaries of the Dnieper River, is deteriorating today due to man-made impact. This leads to a deterioration of water quality and the regime of its river runoff.